Investigation on Circadian Regulation of Four-Primary LED Display Differed in People by GA - Wenhui Li; Junying Li; Yating Feng; Yi Lin; Haoyang Liu; Ruoping Lian; Qinzhen Lin; Jingyi Cui; Zixin Huang; Yaling Chai; Ziquan Guo; Lili Zheng; et al. (IEEE Photonics Journal)
The concept of human-centric lighting is gradually emerging. People no longer only consider the lighting function of light, but also begin to pay attention to the comfort and health of light. In this article, we perform an investigation on the circadian regulation of four-primary light-emitting diode (LED) based displays for the people with various ages from 1 year old to 100 years old. The double-Gaussian function is used to mimic the spectral power distribution of monochromatic LED. The main figures of merit of LED display performance are color gamut of Rec. 2020, luminous efficacy of radiation, correlated color temperature (CCT), and also non-visual parameters, such as circadian stimulus and melanopic efficacy of luminous radiation provided by Commission Internationale de l'Eclairage (CIE) standard. Then, the genetic algorithm is adopted for performing the spectral optimization of four-primary LED display while many constraint conditions are set, such as CCT values (2700 K and 6500 K), CCT tolerance, and color distance (Duv < 0.01) in the CIE 1960 UCS color space. Related results of visual and non-visual characteristics are also compared with those of three-primary LED displays. This work would pave a way for the development of healthy four-primary LED display in consideration of various ages of people.